Hubungan Gaya Kepimpinan dengan Kepuasan Kerja: Kajian Kes di Hotel Oliver, Danok, Thailand - Afnan, Cheda Oh (2011)
This study aims to look at the leadership style of supervisors and job satisfaction in the district Danok, Thailand. This study specifically to identify the leadership style of supervisors based on the views of workers' job satisfaction. This study used a survey method and data obtained from questionnaires using a five point Likert scale. Measuring instrument "Leader Behavior Description Questionnaire" (LBDQ) was used to measure the structural dimensions of leadership style of supervisors and the dimensions of the consideration. Measuring instrument used to measure job satisfaction levels of job satisfaction on the leadership style of supervisors of two dimensions. The sample consisted of 37 workers from the Hotel Oliver, Danok, Thailand. Samples were chosen randomly. Data processing involves the measurement of the frequency of descriptive statistics, mean, standard deviation and percentage. Based on available research the leadership style of supervisors in the two dimensions of structure and consideration dimensions are low in the eyes of employees. Most items in both dimensions are less than 3.00 min. This indicates that the supervisor at the hotel Oliver studied about the leadership style of the two dimensions of the force that resulted in a moderate level of job satisfaction.